Hydro-Resource Management and Conservation in the Teachings of the Holy Prophet Muhammad (P.B.U.H) - Dr. Muhammad Hafeez ur Rahman (Seerat Studies, 2023)
The world is facing a severe disquietude about water scarcity, which is feared to lead to not only local or global chaos and conflicts, but also to bloody “war on waters”. Scarcity and misuse of fresh water pose a serious and growing threat to sustainable development and protection of the environment, and the humans as well. Islam as the second largest religion on the planet, with The Holy Prophet Muhammad (P.B.U.H.)as the sole means and source of Divine guidance from Allah Almighty, lead us to the understanding of importance of the Prophetic injunctions regarding the management and conservation of the hydro-resources. The scope of this article is to inquire and elaborate the above mentioned point, for which verses from the Holy Qur’an, along with qoutations from Ahadith and Seerah literature have been taken as data and studied. The article ends with the conclusion that: The injunctions of the Holy Qur’an, and the Holy Prophet (P.B.U.H.), clearly teach about the importance of water for life on earth, both for humans and animals as well. Various Ahadith of the Holy Prophet(P.B.U.H.) teach about the water management for human needs and agricultural use, local and trans-boundary management, even for animals; with prohibitions regarding monopolizing, polluting, and wastage of precious hydro-resources. It was recommended for further study that: A comparative study should be conducted to get acquainted by the teachings of other religions about the subject, and The teachings of the Holy Prophet (P.B.U.H.) should be explored and brought to surface regarding the management and conservation of other natural resources with collective environmental protection and preservation. The qualitative approach is adopted in this analytical study. The published authentic data including, academic books, websites (after careful evaluation and assurance of their validity and reliability), alongside the Holy Qur’an and the books of Ahadith primarily, were used during the study. In addition, the academic consultation with senior scholars was also involved in this important study.